Implementasi Gateway berbasis NRF24L01 dan ESP8266 pada Protokol Message Queue Telemetry Transport - Sensor Network (MQTT-SN) - Harry Mulya; Sabriansyah Rizqika Akbar; Edita Rosana Widasari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Wireless Sensor Network (WSN) is a wireless network that consists of multiple sensor nodes. WSN can be implemented using a Message Queue Protocol Telemetry Transport (MQTT). MQTT is a protocol that runs of the TCP / IP protocol, so each node that doesn't have a network interface can't use this protocol. Message Queue Telemetry Transport protocol - Sensor Node (MQTT-SN) was created to connect the devices. The gateway is an intermediary between the sensor nodes that run in the MQTT-SN protocol with the broker that runs on the MQTT protocol. Advertisement and discovery is a mechanism used for the client to traces the identity of the gateway, so the client can connect with the gateway. This mechanism is very important because it is the first process before doing other processes such as publishing process. Therefore, this research proposed to implement the mechanism on microcontroller arduino pro-mini and NRF24L01 as communication module. The result of this research is the client able to recognize the existing gateway ID and gateway managed to pass data onto the client to the broker, which marked the receipt of the data by the subscriber.